A person in a virtual reality: some tendencies of changes in an inner life - Pischikov, Volodymyr; Холін, Михайло Максимович (Actual Problems of Mind, 2017)
The paper investigates the essence of a virtual reality as a phenomenon. The authors rethink the changes and their tendencies which the virtual reality introduces into the inner life of a person.